2017
DOI: 10.1016/j.ymthe.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of an Entire Chromosome Using CRISPR/Cas9

Abstract: CRISPR/Cas9 genome editing can facilitate efficient deletion of genomic region, but it has not been used to delete an entire chromosome. Here, Adikusuma et al. show proof-of-concept for efficient CRISPR-mediated selective chromosome deletion by removing the centromere or shredding the chromosome arm in mouse embryonic stem cells and zygotes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 9 publications
(15 reference statements)
1
62
1
1
Order By: Relevance
“…Recently, various genomic modifications with CRISPR/Cas9 technology have been reported, including genomic translocation, inversion, chromosome elimination, single point mutation and knock‐in . Combining these genome‐editing technologies with the RC platform will further facilitate diverse cancer modeling and functional assays in vivo, which should deepen our understanding of the mechanisms that govern various biological phenomena in mammals in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various genomic modifications with CRISPR/Cas9 technology have been reported, including genomic translocation, inversion, chromosome elimination, single point mutation and knock‐in . Combining these genome‐editing technologies with the RC platform will further facilitate diverse cancer modeling and functional assays in vivo, which should deepen our understanding of the mechanisms that govern various biological phenomena in mammals in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that a DSB induced by even a single gRNA can result in the allele-specific removal of a chromosome in human embryos. Previous studies in mouse embryos demonstrated elimination of sex chromosomes by targeting Cas9 to centromeric repeats of the Y chromosome, or to multiple locations on the same chromosome (Adikusuma et al, 2017;Zuo et al, 2017). The finding that a single Cas9 induced cut can result in such outcome in human embryos suggests species-specific differences in repair or checkpoint control.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies using genetic engineering have revealed the possibility of performing aneuploidy therapy in cultured cells. Here, we summarize some of the main studies aimed at eliminating an entire chromosome using the Cre/loxP system [79][80][81][82][83][84][85], the TKneo transgene for positive and negative antibiotic selection [86], CRISPR/Cas9 system-mediated multiple cleavage [87,88], and zinc finger nuclease (ZFN)-mediated knock-in of the XIST gene to silence one copy of chromosome 21 [89] (cited in Table 2).…”
Section: Gene Targeting-mediated Chromosome Eliminationmentioning
confidence: 99%
“…To eliminate extra chromosomes, multiple guide RNAs of the CRISPR/Cas9 system for introducing DNA double-strand breaks (DSBs) into the target site are designed for an entire region of the target chromosome [95][96][97][98][99]. Adikusuma et al [88] used this strategy to delete the mouse Y chromosome in vitro and in vivo ( Figure 1D). Guide RNAs corresponding to repetitive sequences (from 40 to 140 tandem repeats) of the centromere and long arm of chromosome Y were used in their study.…”
Section: Crispr/cas9 System To Introduce Multiple Dna Cleavages For Tmentioning
confidence: 99%